2020
DOI: 10.1089/thy.2019.0719
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Health and Economic Benefits of Universal Salt Iodization Programs to Correct Iodine Deficiency Disorders

Abstract: Background: There has been tremendous progress over the past 25 years to control iodine deficiency disorders (IDDs) through universal salt iodization (USI). In 2019, using the median urinary iodine concentration (MUIC), only 19 countries in the world are classified as iodine deficient; in contrast in 1993, using the total goiter rate (TGR), 113 countries were classified as iodine deficient. However, few analyses have tried to quantify the global health and economic benefits of USI programs, and the shift from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 22 publications
0
30
0
2
Order By: Relevance
“…Iodine supplementation through salt iodization, implemented by the WHO and the International Council for the Control of Iodine Deficiency Disorders (ICCIDD, now Iodine Global Network), is a worldwide, effective strategy for preventing iodine deficiency-related problems. Its safety and efficacy profile has been extensively investigated, and benefits far outweigh the potential iodine-induced risks [ 17 , 18 ]. Iodine prophylaxis through iodized salt has been shown to modulate the pattern of thyroid diseases and also to exert a pivotal role in abating iodine deficiency disorders (IDD) [ 19 , 20 ].…”
Section: Introduction: Thyroid Autoimmunity and Iodinementioning
confidence: 99%
“…Iodine supplementation through salt iodization, implemented by the WHO and the International Council for the Control of Iodine Deficiency Disorders (ICCIDD, now Iodine Global Network), is a worldwide, effective strategy for preventing iodine deficiency-related problems. Its safety and efficacy profile has been extensively investigated, and benefits far outweigh the potential iodine-induced risks [ 17 , 18 ]. Iodine prophylaxis through iodized salt has been shown to modulate the pattern of thyroid diseases and also to exert a pivotal role in abating iodine deficiency disorders (IDD) [ 19 , 20 ].…”
Section: Introduction: Thyroid Autoimmunity and Iodinementioning
confidence: 99%
“…The thyroid size is a very useful indicator for assessing the severity of iodine deficiency, but it is also used to control the initiation of a preventive strategy for control of iodine deficiency [30]. Our result showed that the average thyroid volume for the whole group of pregnant women was 8.94±2.62 mL, median 8.65 (minimum 0.26 -maximum 23.04).…”
Section: Discussionmentioning
confidence: 68%
“…To minimize the impact of IDD, the adoption of universal salt iodization (USI) program is recommend in all countries and there has been major global progress to the elimination of IDDs [ 13 ]. For instance, the global prevalence of clinical IDDs fell from 13.1% in 1993 to 3.2% in 2019, and 720 million cases of clinical IDDs have been prevented by USI (a reduction of 75.9%) [ 14 ] and the proportion of households consuming iodized salt increased from 70% in 2000 to 88% in 2019 low-income countries [ 13 ]. Although this substantial progress has been made over the last several decades towards iodized salt consumption, still it is under the recommendation of the World Health Organization(at least 90% of households should consume iodized salt) [ 8 ] and hence, iodine deficiency remains a significant health problem in developing countries [ 15 ].…”
Section: Introductionmentioning
confidence: 99%